WOMEN IN TECH IN THE MIDDLE EAST: EXPERIENCES AND POSSIBLE SOLUTIONS TO THEIR CHALLENGES - Ikhuoria, Rita Sharon (Digital Repository of Theses, 2023)
This study aimed to assess women's challenges in tech in the Middle East and possible solutions to mitigating these challenges. First, an in-depth literature review using several academic databases was conducted to understudy the study's objectives. Thirteen In-depth Interviews were conducted among women who work in different technology industries in Yemen (8), Israel (4), and Iran (1). The first participant was identified through an internet search for women in the technology industry in Yemen, and then snowballing was used to recognize other participants. As disclosed by participants, the challenges facing women in tech included personal beliefs or opinions, family inclinations, societal norms, sociocultural and organizational structure and practices, the low value attached to education, perception of child care and women's role, and unfavorable work hours and difficulty getting managerial positions. Identified factors that facilitated the women's interest and choice of technology education and industry included that tech jobs came with a good salary, support from family, societal influence, and good academic performance in courses like mathematics. Participants and other related studies have pointed out some ways to deal with these problems. These include giving young women who want to work in tech access to role models and grants and scholarships for tech education, making sure that the government and organisations have policies that help women do well in the field, raising awareness to change people's negative ideas about women in tech, and giving young women who want to work in tech social support. The success of women already in the tech industry will depend on a multi-pronged approach that addresses their challenges by implementing policies that will address the gender gap in tech holistically while tackling issues from the home to the society to the work settings. (Mukhwana et al., 2020). Approaches that remove barriers to women's success in technology at the individual, family, and social levels, as well as in the workplace, as well as policies that protect gender parity in technology in education and career prospects, are strongly recommended.